AI AND PERSONAL DATA PRIVACY IN THE U.S: BALANCING CUSTOMER CONVENIENCE WITH PRIVACY COMPLIANCE. - Hakeemat Ijaiya; Israel Adekunle Adeniyi (ABUAD Law Journal, 2024)
The proliferation of Artificial Intelligence (AI) across various industries in the United States has ushered in an era of transformative technological advancements, which has provided businesses with the ability to enhance customer experiences and drive operational efficiencies. However, this development has brought about increased challenges in preserving the privacy and security of personal data in the US. The paper examines the need to balance customer convenience with privacy compliance within the context of AI and personal data privacy in the U.S. The paper also examines the state of data privacy and concerns arising from the use of AI. It assesses the key legal frameworks in the U.S. and their adequacy to regulate AI in light of data privacy. The paper employs a doctrinal research methodology to examine the laws and identify the challenges arising from the regulatory gaps in AI and personal data privacy. The paper finds that there are challenges stemming from the lack of alignment between existing legal frameworks and the evolving AI technologies, especially in relation to data collection, data anonymization, and consent management. The paper recommends the need to reform existing laws to be up to date with the evolving capabilities of AI. The paper concludes that the growth of AI in relation to personal data privacy presents both opportunities and challenges.